PENERAPAN STRATEGI PEMBELAJARAN PREDICT DISCUSS EXPLAIN OBSERVE DISCUSS EXPLAIN (PDEODE) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KOLOID DI KELAS XI MIA MA DARUL HIKMAH PEKANBARU - Aditya Eka Septiriana; Elva Yasmi Amran; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the improvement of student achievement by applying predict discuss explain observe discuss explain (PDEODE) learning strategy to improve student’s of colloid in class XI MIA MA Darul Hikmah Pekanbaru. The study was an experiment with randomized control group pretest-posttest. The sample in this research is class XI MIA 2 as experiment class which is determined randomly after normality test and homogeneity test. The experimental class is treated with the implementation of predict discuss explain observe discuss explain (PDEODE) learning strategy. Data analysis for hypothesis testing is done using right-t test. Based on the results of data analysis obtained tcount = 2,16 and ttable = 1,67 with = 0,05, dk = 57. tcount > ttable is 2,16 > 1,67 means the implementation of predict discuss explain observe discuss explain (PDEODE) learning strategy can improve student learning achievement on colloid subject at class XI MIA MA Darul Hikmah Pekanbaru.Keywords : Predict discuss explain observe discuss explain (PDEODE) learning strategy, Learning achievement, Colloid